Preparation of Tourmaline-containing Functional Copolymer p(TUC/BA/MMA) and Its Performances. Issue 2 (2nd April 2016) - Li, Yunhua; Hu, Yingmo; Liu, Yuhang; Li, Mengcan; Liu, Quan; Hou, Chunyan
ABSTRACT: In order to develop the tourmaline-containing functional polymer, the double-bond-containing undecenoyl group was introduced onto the surface of tourmaline to synthesize a polymerizable organic tourmaline undecylenate (TUC) by the surface modification of tourmaline with 10-undecenoyl chloride. The TUC was then copolymerized with butyl acrylate (BA) and methyl methacrylate (MMA) to obtain the tourmaline-containing functional copolymer p(TUC/BA/MMA), which showed an excellent storage stability. The structures of TUC and its copolymers were characterized by means of IR, XRD, SEM, and EDX. The results indicated that the tourmaline-containing functional copolymer displayed excellent mechanical, far-infrared radiating, and negative ion releasing performances.